Preventing Sexual Violent Behavior - Muhtar Arifin; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2022)
The purpose of this study was to determine the comparison between the concept of Permendikbudristek and the concept of Islam in an effort to prevent the occurrence of sexual violence behavior. This research is included in library research with maqashid shari'ah approach. The data collected in this study using the document study method. Among the results obtained arePermendikbudristek no. 30 of 2022 has similarities and differences with Islamic law in regulating relations between men and women. Among the forms of the equation is in terms of its purpose, namely to realize the general benefit and its formulation. While the difference between the two laws is in terms of the origin of the rules, in terms of accuracy in choosing pronunciation and in terms of willingness in terms of sexual violence behavior. In the Ministerial Regulation there are several things which are cases that should not be done between men and women, but when they are done voluntarily, they are not categorized as violating the rules. Whereas in Islam, these things even though they are consensual are still prohibited. The author concludes that the phrase "without the victim's consent" can lead to various mafsadat, which is contrary to the maqashid shari'ah in terms of hifdzud diin (religious protection), hifdzun nasl (protection of offspring), hifdzul 'irdh (keeping of honor) and hifdzul mal (protection of property). . This study recommends improving the text of the regulation, especially on phrases that contain many pros and cons.